Invasive hemodynamic evaluation in patients with mechanical aortic valves. Issue 1 (23rd January 2013) - Kiefer, Todd L.; Wang, Andrew; Harrison, J. Kevin
<x xml:space="preserve">Abstract</x> Invasive hemodynamic evaluation in the patient with a mechanical aortic valve has in the past required transseptal or apical left ventricular puncture in order to obtain left ventricular pressure measurements. Over the last few years, several case reports have described the feasibility of using a coronary pressure‐sensing guidewire to cross mechanical prosthetic aortic valves. In the current manuscript, we report four cases in which the use of a pressure‐sensing guidewire was utilized for invasive hemodynamic diagnostic evaluation in patients with mechanical aortic valves. Furthermore, we present a detailed description of the technical approach to this technique and the limitations of this approach. © 2013 Wiley Periodicals, Inc.